Interpreting sperm DNA damage in a diverse range of mammalian sperm by means of the two-tailed comet assay - Cortés-Gutiérrez, Elva I.; López-Fernández, Carmen; Fernández, José Luis; Dávila-Rodríguez, Martha I.; Johnston, Stephen D.; Gosálvez, Jaime (Frontiers in Genetics, 2014)
Key Concepts The two-dimensional Two-Tailed Comet assay (TT-comet) protocol is a valuable technique to differentiate between single-stranded (SSBs) and double-stranded DNA breaks (DSBs) on the same sperm cell. Protein lysis inherent with the TT-comet protocol accounts for differences in sperm protamine composition at a species-specific level to produce reliable visualization of sperm DNA damage. Alkaline treatment may break the sugar–phosphate backbone in abasic sites or at sites with deoxyribose damage, transforming these lesions into DNA breaks that are also converted into ssDNA. These lesions are known as Alkali Labile Sites “ALSs.” DBD–FISH permits the in situ visualization of DNA breaks, abasic sites or alkaline-sensitive DNA regions. The alkaline comet single assay reveals that all mammalian species display constitutive ALS related with the requirement of the sperm to undergo transient changes in DNA structure linked with chromatin packing. Sperm DNA damage is associated with fertilization failure, impaired pre-and post- embryo implantation and poor pregnancy outcome. The TT is a valuable tool for identifying SSBs or DSBs in sperm cells with DNA fragmentation and can be therefore used for the purposes of fertility assessment. Sperm DNA damage is associated with fertilization failure, impaired pre-and post- embryo implantation and poor pregnancy outcome. A series of methodologies to assess DNA damage in spermatozoa have been developed but most are unable to differentiate between single-stranded DNA breaks (SSBs) and double-stranded DNA breaks (DSBs) on the same sperm cell. The two-dimensional Two-Tailed Comet assay (TT-comet) protocol highlighted in this review overcomes this limitation and emphasizes the importance in accounting for the difference in sperm protamine composition at a species-specific level for the appropriate preparation of the assay. The TT-comet is a modification of the original comet assay that uses a two dimensional electrophoresis to allow for the simultaneous evaluation of DSBs and SSBs in mammalian spermatozoa. Here we have compiled a retrospective overview of how the TT-comet assay has been used to investigate the structure and function of sperm DNA across a diverse range of mammalian species (eutheria, metatheria, and prototheria). When conducted as part of the TT-comet assay, we illustrate (a) how the alkaline comet single assay has been used to help understand the constitutive and transient changes in DNA structure associated with chromatin packing, (b) the capacity of the TT-comet to differentiate between the presence of SSBs and DSBs (c) and the possible implications of SSBs or DSBs for the assessment of infertility.